2016
DOI: 10.1111/hae.12996
|View full text |Cite
|
Sign up to set email alerts
|

Medical co‐morbidities of patients with haemophilia: pain, obesity and hepatitis C

Abstract: Clinical care of patients with haemophilia (PWH) has progressed rapidly over the past decade. Current therapy has allowed patients with haemophilia to live longer and many patients are now experiencing the co-morbidities of the general population. In this review article, we focus on three common diseases states that affect PWH: chronic pain, obesity and hepatitis C. Pain has been a co-morbidity for many years and PWH often have unusual needs for chronic pain relief compared to the general population. Obesity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
0
17
0
3
Order By: Relevance
“…Antiviral therapy with direct-acting antivirals (DAAs) leads to sustained virological response (SVR) in more than 95% of patients with minimal adverse events and high adherence rates. 4,5 Patients with HCV with inherited bleeding disorders are a valuable cohort that enables reliable studying of slow progression of chronic HCV infection. Evidence on the risk and complications of HCV infection after long-term exposure is limited.…”
Section: Hepatitis C Infection In a Greek Population With Inherited Bmentioning
confidence: 99%
“…Antiviral therapy with direct-acting antivirals (DAAs) leads to sustained virological response (SVR) in more than 95% of patients with minimal adverse events and high adherence rates. 4,5 Patients with HCV with inherited bleeding disorders are a valuable cohort that enables reliable studying of slow progression of chronic HCV infection. Evidence on the risk and complications of HCV infection after long-term exposure is limited.…”
Section: Hepatitis C Infection In a Greek Population With Inherited Bmentioning
confidence: 99%
“…A dramatic change in the treatment of HCV is however upon us with multiple new highly effective agents such as sofosbuvir, daclatasvir, ledipasvir, simeprevir, ombitasvir, paritaprevir and dasabuvir . The current interferon‐free treatments which are often once daily oral treatments for 8–12 weeks achieve clearance in excess of 95% with virtually no side effects.…”
mentioning
confidence: 99%
“…Recent advances in the treatment of hepatitis C should substantially decrease the risk of CLD due to HCV infection in hemophilia patients. (12) In severe forms of cirrhosis, Soria et al (13) found that fibrinogen levels tend to decrease and abnormal fibrinogen molecules can be detected. Fulminant hepatic failure caused by HEV is accompanied by disseminated intravascular coagulation.…”
Section: The State Of the Hemostatic System In Cldmentioning
confidence: 99%